ON THE INTERRELATIONSHIP OF STRUCTURAL CHANGES DURING FATIGUE OF CARBON STEEL WITH THE STRUCTURAL FEATURES OF THE FRACTURE SURFACES - Vakulenko, I. O. (Science and Transport Progress, 2010)
For the rail axle steel the regular changes of structure during the fatigue test in dependence on strength amplitude are presented.